Enhancing Number Recognition Through Concrete Media-Based Project Learning: An Action Research Study with Children at Risk of Learning Difficulties - Sumartin, Santy; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Number recognition represents a fundamental cognitive milestone in early childhood development, yet children with learning difficulties often struggle with abstract mathematical concepts. This study investigated the effectiveness of concrete media-based project learning in enhancing number recognition abilities among kindergarten children at risk of learning difficulties. An action research design following the Kemmis and McTaggart model was implemented over three iterative cycles from January to May 2025. The participant was a 5-6 year-old child identified with learning difficulties at TK Negeri Pembina, East Kalimantan, Indonesia. The intervention employed Project-Based Learning methodology through a "Mini Market" theme utilizing concrete manipulatives including toy fruits, play money, price cards, and calculators. Data collection involved structured oral assessments measuring numerical symbol recognition, quantity-symbol matching, and project participation, alongside qualitative observations. Performance was evaluated using a four-point scale, with success criteria set at ≥76% achievement. Substantial performance improvement was achieved from baseline 25% to final assessment 91.6%, representing a 66.6 percentage point increase. Progressive gains were documented across cycles: Cycle I (25% to 58.3%), Cycle II (66.6% to 75%), and Cycle III (83.3% to 91.6%). Qualitative observations revealed enhanced engagement, increased confidence, and improved social interaction during mathematical activities. The participant progressed from requiring extensive teacher assistance to independent task completion and peer collaboration. Concrete media-based project learning significantly enhanced number recognition abilities in children with learning difficulties. The systematic, multi-cycle intervention provides a replicable framework combining Piaget's developmental theory with contemporary project-based pedagogical approaches. These findings support inclusive educational practices emphasizing differentiated instruction through authentic, contextualized learning experiences.